2018
DOI: 10.1016/j.ijnurstu.2017.09.010
|View full text |Cite
|
Sign up to set email alerts
|

International practice settings, interventions and outcomes of nurse practitioners in geriatric care: A scoping review

Abstract: This review demonstrates improved or non-inferiority results of nurse practitioner care in older people across settings. More well-designed, rigorous studies are needed particularly in relation to costs. The results of this review could be used for future systemic review of effectiveness of NP care specific to older people. Despite the demonstrated NP role value, barriers to implementing the nurse practitioner role persist internationally and more work is needed to develop and promote these roles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 112 publications
3
66
0
2
Order By: Relevance
“…There is a growing interest in the implementation of the role of ANPs (Casey, O’Connor, Cashin, et al, ; Casey, O’Connor, Nicholson, et al, ; Chavez et al, ; O'Connor et al, ; Woo, Lee, & Tam, ). There is a growing interest in the development and implementation of the role of ANPs and AMPs (Chavez, Dwyer, & Ramelet, ; O'Connor et al, ; Woo et al, ). Franks and Howarth () found that similar roles were enabled by the high public priority, legislative, policy support and support from organisational leaders and managers.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing interest in the implementation of the role of ANPs (Casey, O’Connor, Cashin, et al, ; Casey, O’Connor, Nicholson, et al, ; Chavez et al, ; O'Connor et al, ; Woo, Lee, & Tam, ). There is a growing interest in the development and implementation of the role of ANPs and AMPs (Chavez, Dwyer, & Ramelet, ; O'Connor et al, ; Woo et al, ). Franks and Howarth () found that similar roles were enabled by the high public priority, legislative, policy support and support from organisational leaders and managers.…”
Section: Discussionmentioning
confidence: 99%
“…Registered nurses are healthcare leaders and hold the greatest accountability for the care of residents in RACFs; as a result, they play a vital role in promoting nurse‐led interventions in the advancement of resident well‐being (Chavez, Dwyer, & Ramelet, ; Kiljunen, Välimäki, Kankkunen, & Partanen, ). Nurse‐led interventions are defined as those where nurses are the principal leading personnel in developing and delivering the intervention, and nurses use their professional expertise to tailor the intervention (Richardson & Cunliffe, ).…”
Section: Introductionmentioning
confidence: 99%
“…International reviews have evaluated the effectiveness of care given to residents (patients in LTC) by primary healthcare nurse practitioners (NPs). These reviews showed that NPs in LTC improve the quality of care delivered to residents and increase knowledge of healthcare team members (Chavez, Dwyer, & Ramelet, 2018;Donald et al, 2013;Morilla-Herrera et al, 2016).…”
Section: Introductionmentioning
confidence: 99%